Dialect Data Processing in a Corpus of Ukrainian Dialect Texts (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The paper is devoted to the methodology of building a Corpus of Ukrainian Dialect Texts (CorUDiT) in the framework of the Corpus of Texts of the Ukrainian Language (CTUL). We pay special attention to the peculiarities of the representation of dialect texts in CorUDiT. The testing of the systematic treatment of dialect texts is done on the author’s dialect text collection representing the West Volynian dialect region. Our investigation also focuses on the future trends of the development of CorUDiT.
Keywords: dialect text; corpus; marking; Ukrainian language